Bisecting GlcNAc expression by bone marrow stromal cells modulates TGF-β1-driven macrophage polarization in myeloid leukemias - Jingjing Feng; Junjie Gou; Yi Wang; Wei Wei; Yihan Ma; Xueting Ren; Chongfu Zhao; Xiaoliang Cheng; Lei Lei; Zengqi Tan; Feng Guan; Xiang Li (Haematologica)
Accumulating evidence have highlighted the critical role of tumor-associated macrophages (TAMs) in promoting immune evasion and disease progression in acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS). Combined single-cell RNA sequencing, flow cytometry, and immunohistochemistry studies of the innate immune compartment in bone marrow of MDS/AML reveal a shift toward a tumor-supportive M2-polarized macrophage as well as the expression of programmed cell death-ligand 1 (PD-L1) in this cell lineage. We found the leukemic stroma cells with high level of TGFβ1 secretion can determine TAMs toward M2-polarized subtype. Further mechanistic investigations revealed that bone marrow stromal cells with specific glycans, reduced bisecting N-acetylglucosamine (GlcNAc) levels, in MDS/AML promoted M2-polarized subtype through the secretion of TGFβ1, which elevated PD-L1 expression and thereby impaired CD8+ T cell function. Our study provides insights into the mechanisms of selectively modifying specific glycans in bone marrow stroma cells may contribute to targeting strategies aimed at the tumor microenvironment.